Mixing in Feminism. (14th March 2016) - Vesey, Alyxandra
Abstract : This article argues that music is a meaningful resource within feminist and queer communities that supplements traditional modes of activist work and political commentary. To do so, it analyzes guest-curated playlists for feminist- and queer-oriented multimedia sites Bitch Media and Homoground by offering thick description of a representative playlist from each site's archive in order to interpret their political motives. Such mixing practices represent playlists' civic engagement in two ways. First, they demonstrate fan identification through producers' efforts to assemble feminist critiques from music by recording artists who represent various eras and genres and identify as female, queer, and/or people of color. Second, it indicates digital media's potential for community-building.